Stabilising frozen dairy mousses by low molecular weight gelatin peptides. (October 2016) - Duquenne, Barbara; Vergauwen, Bjorn; Capdepon, Claude; Boone, Marijn A.; De Schryver, Thomas; Van Hoorebeke, Luc; Van Weyenberg, Stephanie; Stevens, Paul; De Block, Jan
Abstract: The effect of low molecular weight gelatin peptides on the shrinkage of thawed mousses was investigated. Changes promoted by freezing-thawing processes were evaluated through texture and volume measurements and through X-ray analysis of the bubble distribution. Freezing provoked collapse of the standard reference recipe mousse and of the reference recipe mousse with 2% milk powder added, but samples containing 2% gelatin peptides showed no shrinkage. The bubble size and bubble number distribution of the different mousses were measured based on high-resolution X-ray tomography. Results indicated that the volume losses experienced by the controls were almost entirely caused by the disappearance of air bubbles having a diameter smaller than 50 μm. Hence, this fraction of over-pressurised air bubbles is extra stabilised by the matrix due to the additional presence of gelatin peptides. Moreover, gelatin peptides were found to inhibit ice crystal growth, which resulted in smaller ice crystals that are believed to be less destructive to the microstructure of the freeze-thawed mousses. Graphical abstract: Highlights: Gelatin peptides protect frozen mousses against collapse and volume loss. Gelatin peptides fortify the microstructure by stabilising air bubbles. Gelatin peptides have a most profound effect on the <50 μm fraction air bubbles. Gelatin peptides inhibit ice crystal growth.